Measuring the Impact of a Trade Dispute with a Supply-side Shock Using a Supply-driven Input-Output Analysis: Korea-Japan Dispute Case - Dongseok Kim (KDI Journal of Economic Policy, 2021)
The purpose of this paper is to measure the impact of the recent Korea-Japan trade dispute on the Korean economy using supply-driven input-output analysis. In July 2019, Japan announced the decision to tighten the export control of three materials which are indispensable in the manufacturing of semiconductors and electronic display panels. Japan's decision directly affects production in Korea's semiconductor and display sectors and is hence not a demand shock. For this reason, a standard demand-driven input-output analysis is not valid despite the fact that it can still be applied. The impact of Japan's decision on Korea's aggregate and individual sectors' gross output, GDP and employment were computed using both methods.
Keywords: D57; F13; F14; 330; Supply-driven Input-Output Analysis; Demand-driven Input-Output Analysis; Korea-Japan Trade Dispute